PENGARUH KEPEMIMPINAN SPIRITUAL TERHADAP KEPUASAN KERJA KARYAWAN MELALUI WORK ENGAGEMENT SEBAGAI VARIABEL MODERASI - Wella Manovia; Iwan Setiawan Adji; Edy Purwo Saputro (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the influence of spiritual leadership on employee job satisfaction by considering the role of work engagement as a moderating variable at RS PKU Muhammadiyah Karanganyar. Spiritual leadership is viewed as a leadership style that emphasizes ethical values, spirituality, and exemplary behavior in influencing organizational members. These values are expected to provide meaning and a sense of belonging to employees, thereby positively impacting job satisfaction. The study employs a quantitative approach with an associative-causal research design, utilizing data collection through research instruments and statistical analysis. The results show that spiritual leadership, which includes vision, faith/hope, and altruistic love, has a significant and positive effect on employee job satisfaction. Furthermore, work engagement which comprises vigor, dedication, and absorption also shows a significant influence on job satisfaction. In addition, work engagement acts as a moderating variable that strengthens the relationship between spiritual leadership and job satisfaction. This means that higher levels of employee engagement enhance the positive impact of spiritual leadership on job satisfaction. These findings highlight the importance of spiritual leadership and the need to cultivate a work environment that fosters full employee involvement.